Comparing Clinical Outcomes on Oncology Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Implantation: A Systematic Review and Meta-Analysis - Song, Yumeng; Wang, Yutong; Wang, Zuoxiang; Xu, Chang; Dou, Jingshen; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Objective To compare the clinical outcomes of cancer and non-cancer patients with severe aortic stenosis (AS) after transcatheter aortic valve implantation (TAVI). Methods A computer-based search in PubMed, EMbase, The Cochrane Library, CBM, CNKI, and Wanfang databases from their date of inception to October 2021, together with reference screening, was performed to identify eligible clinical trials. Two reviewers independently screened the articles, extracted data, and evaluated their quality. Review Manger 5.3 and Stata 12.0 software were used for meta-analysis. Results The selected 11 cohort studies contained 182,645 patients, including 36,283 patients with cancer and 146,362 patients without cancer. The results of the meta-analysis showed that the 30-day mortality [OR = 0.68, 95%CI (0.63,0.74), I2= 0, P < 0.00001] of patients with cancer in the AS group was lower than those in the non-cancer group; 1-year mortality [OR = 1.49, 95%CI(1.19,1.88), I2= 58%, P = 0.0006] and late mortality [OR = 1.52, 95%CI(1.26,1.84), I2= 55%, P < 0.0001] of patients with cancer in the AS group was higher than those in the non-cancer group. The results of the meta-analysis showed that the stroke [OR = 0.77, 95%CI (0.72, 0.82), I2= 0, P < 0.00001] and the acute kidney injury [OR = 0.78, 95%CI (0.68, 0.90), I2= 77%, P = 0.0005] of patients with cancer in the AS group was lower than those in the non-cancer group. The results of the meta-analysis showed no statistical difference in cardiovascular mortality, bleeding events, myocardial infarction, vascular complication, and device success rate. Conclusion It is more effective and safer in patients with cancer with severe AS who were undergoing TAVI. However, compared with patients with no cancer, this is still high in terms of long-term mortality, and further study of the role of TAVI in patients with cancer with AS is necessary. Systematic Review Registration Identifier [INPLASY CRD: 202220009].